Probing the properties of size dependence and correlation for tantalum clusters: geometry, stability, vibrational spectra, magnetism, and electronic structure. Issue 2 (8th January 2019) - Li, Xibo; Chen, Yuqi; Basnet, Pradip; Luo, Jiangshan; Wang, Hongyan
Abstract : A comprehensive investigation on the equilibrium geometry, relative stability, vibrational spectra, and magnetic and electronic properties of neutral tantalum clusters (Ta n, n = 2–17) was performed using density functional theory (DFT). Abstract : A comprehensive investigation on the equilibrium geometry, relative stability, vibrational spectra, and magnetic and electronic properties of neutral tantalum clusters (Ta n, n = 2–17) was performed using density functional theory (DFT). We perform a study of the size dependence and correlations among those descriptors of parameters, and showed these could provide a novel way to confirm and predict experimental results. Some new isomer configurations that have never been reported before for tantalum clusters were found. The growth behaviors revealed that a compact geometrical growth route is preferred and develops a body-centered-cubic (BCC) structure with the cluster size increasing. The perfectly fitted functional curve, strong linear evolution, and obvious odd–even oscillation behavior proved their corresponding properties depended on the cluster size. Multiple demonstrations of the magic number were confirmed through the correlated relationships with the relative stability, including the second difference in energy, maximum hardness, and minimum polarizability. An inverse evolution trend between the energy gap and electric dipole moment and strong linear correlation between ionization potentials and polarizability indicated the strong correlation between the magnetic and electronic properties. Vibrational spectroscopy as a fingerprint was used to distinguish the ground state among the competitive geometrical isomers close in energy. The charge density difference isosurface, density of states, and molecular orbitals of selected representative clusters were analyzed to investigate the difference and evolutional trend of the relative stability and electronic structure. In addition, we first calculated the ionization potential and magnetic moment and compared these with the current available experimental data for tantalum clusters.